High incidence of stroke in COVID-19 patients - Chen, Jingyu (Aging (Albany NY), 2020)
A retrospective analysis of 11 COVID-19 patients complicated with stroke was performed. It was found that the incidence of stroke in patients with COVID-19 was significantly higher than the average level of the general population (P=0.003), and the D-dimer levels of 11 stroke patients were significantly higher than other patients (P=0.004). The significant increase of D-dimer can be used as an early warning indicator of cerebral infarction. It is critical to have a response plan for treating acute stroke in COVID-19 patients.